ANALYSIS OF THE MARKETING STRATEGY OF HAJJ AND UMRAH (SAHARA) SAVINGS IN AN EFFORT TO INCREASE THE NUMBER OF CUSTOMERS AT BMT NU EAST JAVA PUJER BONDOWOSO BRANCH - Ilham Nuruddin (IJED: International Journal of Economy Development Research, 2023)
Marketing is something that covers all systems that have a relationship with the aim of planning and determining prices to promoting and distributing products (goods or services) that can satisfy consumers. Hajj and Umrah savings products (SAHARA) are savings that use the Mudharabah Mutlaqah contract, namely: (a cooperation agreement between shahibul maal and mudharib). In this regard, this research was carried out with the aim of keeping consumers attracted to the products being released with several strategies that have been implemented. In accordance with the focus of the study, the data search process was carried out using a qualitative research type approach using the literature. This research uses descriptive qualitative research to describe the marketing strategy for Hajj and Umrah savings products (SAHARA) in increasing customer interest at BMT NU Pujer Branch. BMT NU Pujer Branch releases SAHARA products using the mudharabah mutlaqah contract system which aims to make customers' dreams come true. In marketing SAHARA BMT NU Pujer Branch products through direct marketing to the public and other strategies using browsers and advertising. The operational supporting factor for BMT NU Pujer Branch in the Hajj and Umrah Savings (SAHARA) product is the contribution made by MWCNU which is an external supporting factor, while the internal factors are low daily deposits, competitive profit sharing, managed using sharia principles using contracts. Mudlarabah Mutlaqah. Then the inhibiting factors are the lack of potential human resources with knowledge of sharia principles, the elderly factor towards customers, the community's economy declining, lots of competition, and the lack of public trust in NU, especially in the BMT NU Pujer Branch.